2008
DOI: 10.1186/1472-6963-8-133
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive medication prescription patterns and time trends for newly-diagnosed uncomplicated hypertension patients in Taiwan

Abstract: Background: Knowledge of existing prescription patterns in the treatment of newly-diagnosed hypertension can provide useful information for improving clinical practice in this field. The aims of this study are to determine the prescription patterns and time trends for antihypertensive medication in newly-diagnosed cases of uncomplicated hypertension in Taiwan and to compare these with current clinical guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 30 publications
4
44
2
Order By: Relevance
“…[32][33][34][35] However the above pattern is anomalous to other studies conducted by (Tiwari et al; Surapaneni et al) in India, Pittrow et al in Germany and (Lee et al, in China have reported higher prevalence of hypertension in females than in males. 18,26,29,30 This study also reveals that hypertension is more prevalent in elderly patients belonging to age group 40-60 or more. Study conducted by Tiwari et al found most common age group 50-59 years (33.3%) followed by 60-69 years and 40-49 years (26.7%).…”
Section: Discussionmentioning
confidence: 53%
“…[32][33][34][35] However the above pattern is anomalous to other studies conducted by (Tiwari et al; Surapaneni et al) in India, Pittrow et al in Germany and (Lee et al, in China have reported higher prevalence of hypertension in females than in males. 18,26,29,30 This study also reveals that hypertension is more prevalent in elderly patients belonging to age group 40-60 or more. Study conducted by Tiwari et al found most common age group 50-59 years (33.3%) followed by 60-69 years and 40-49 years (26.7%).…”
Section: Discussionmentioning
confidence: 53%
“…The situation in Nigeria is such that healthcare financing is mainly out of pocket payments and often the burden is borne entirely by the individuals affected [9]. Given the growth in healthcare expenditure and the limited resources for healthcare, there is a clear need to explore prescription patterns and trends, in a chronic disease such as hypertension [10].…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines recommend Thiazide diuretics to be prescribed alone or as part of combination therapy for most hypertensive patients without compelling indications [11]. However, most recent published data showed an increasing use of the more expensive Calcium Channel Blockers (CCBs) and Angiotensin Converting Enzyme Inhibitors (ACEIs) despite the lack of evidence to support that they are superior to diuretics and beta blockers in reducing morbidity and mortality of cardiovascular diseases [12]. Despite broad dissemination of the JNC guidelines, prescribing practices have long remained discrepant with recommendations [13].…”
Section: Introductionmentioning
confidence: 99%